Spiritual and Social Constructions in Islamic Pedagogy (Historical Research) - Vachruddin, Vrisko Putra; Nashrullah, Nashrullah; Ahsantudhonni, Ahsantudhonni; Asrohah, Hanun (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
In this article the author constructs spiritual and social values in the Pedagogical Islamic historical perspective. A lack of understanding of Islamic pedagogy makes the negative stigma that Islamic pedagogy is only centered on the development of spirituality only, whereas Islamic pedagogy combines intellectual and spiritual development with interaction in learning. In order to achieve ideal learning, Islam offers the use of traditionalist teaching methods with the aim of forming humans spiritually, which is termed Islamic pedagogy. The idea of islamic pedagogy concept is characterized by the interplay between memorization, oral scientific transmission and writing that supports learning. The practice of Islamic pedagogy education is inseparable from the mystical approach to sacred texts. That is because the Strategy of Islamic pedagogy was formed by the revelation of the Qur'an obtained through hearing as well as Arabic culture from the relationship between memorization (memory) and oral tradition. This research uses historical methods by going through stages, namely; heuristics, source criticism, interpretation and historiography. Memorization and oral tradition were the Arabs' way of spreading knowledge long before the practice of writing was known. Educational environments (mosques, madrasah) are more characterized as spiritual construction. The existence of social interaction in oral and written methods is the basic construction of the formation of social attitudes of students.